Cloud native approach of agile cloud-network converged application delivery - Yong CHEN; Wensheng YAO; Jingxiang CHEN; Huan LIANG; Jing LI (Dianxin kexue)
ion:Cloud-network convergence is the strategy many telecom operators are implementing for the new information infrastructure,as the technicalbasis cloud native technology prompts the capability integration and business innovation.Leveraging the cloud native DevOps tool-chain and methodology becomes the mainstream in cloud application,for agile delivery of high-quality service and bringing the business value.Principles and solutions of leveraging DevOps in cloud-network converged application were given in three aspects:agile process adoption,key technology and DevOps platform establishment,from the view point of telecom operator.Case study of DevOps platform inproduction environment was presented in the end.